Mechanisms of plant phenolic compounds affecting soil nitrogen transformation - Zhaoya Chen; Xinxing Zhang; Ying Huang; Zheng Shi; Haijiao Yao (Alexandria Engineering Journal)
Phenolic compounds, as plant secondary metabolites, possess the ability to regulate soil nitrogen cycling and reduce nitrogen loss. Through the action of soil microorganisms, phenolic substances of varying molecular weights undergo interconversion, continuously influencing soil nitrogen transformation. Yet, existing research predominantly focuses on isolated compounds or processes, lacking a holistic examination. To elucidate the primary mechanisms by which various phenolic compounds influence nitrogen transformation in soil, the present study collected relevant literature published up to May 2024 from multiple databases including Web of Science and China National Knowledge Infrastructure (CNKI). Data extracted from these sources were subsequently analyzed using MetaWin software to conduct a meta-analysis.The specific findings are as follows: H-CT significantly reduce MNR, PNR, DNR, and the concentrations of DON, NH4+-N, and NO3--N, with respective effect sizes of 63.4 %, 53.8 %, 19.9 %, 12.1 %, 36.1 %, and 6.8 %. Compared to HT, CT exhibit a stronger inhibitory effect on MNR and PNR, and H-CT are more effective than their L-CT. Tannin degradation products, such as CE, primarily reduce NO3--N content by inhibiting PNR (Effect size: −47.1 %). PA mainly decrease soil inorganic nitrogen content by inhibiting urease activity (Effect size: −15.2 %). In conclusion, phenolic substances effectively delay soil nitrogen transformation and contribute to the reduction of soil nitrogen loss. Furthermore, high molecular weight phenolic substances exhibit potential as biological nitrogen regulators. This study has significant scientific implications for a deeper understanding of plant-soil interactions, discovering suitable biogenic nitrogen regulators, and promoting cross-system recycling of organic waste.